Elasticity Analysis for Three Animal Protein Resources in Indonesia - Wahyuni, Daru; Purnastuti, Losina; Mustofa, Mustofa (Jurnal Economia, 2016)
Abstract: Elasticity Analysis for Three Animal Protein Resources in Indonesia. This study aimed to analyze the behavior of household demand on three sources of animal protein (fish, beef, and chicken) were associated with different household characteristics and analyze the response of households in Indonesia to changes in price and income on the consumption of fish, beef, and chicken. Almost Ideal Demand System (AIDS) was adopted in this study, using data from the Indonesia Family Life Survey wave 4 (IFLS 4). Total number of the household analyzed in this study amounted to 839 households. The results showed that partially price of fish, beef prices, household expenditure, geographic region, and number of family members affect the share of expenditure fisheries products, chicken, and beef. The results implied that Price elasticity of demand for demand for fish, beef, and chicken were categorized as inelastic. While the income elasticity for beef and chicken were elastic, furthermore income elasticity for fish was inelastic.Keywords:  Almost Ideal Demand System (AIDS) model, demand price elasticity, cross elasticity of demand, income elasticity of demand.Abstrak: Analisis Elastisitas Tiga Bahan Pangan Sumber Protein Hewani di Indonesia. Penelitian ini bertujuan untuk menganalisis perilaku permintaan rumah tangga atas tiga sumber protein hewani (ikan, daging sapi, dan daging ayam) dikaitkan dengan karakteristik rumah tangga yang berbeda dan menganalisis respon rumah tangga di Indonesia terhadap perubahan harga dan pendapatan pada konsumsi ketiga komoditas tersebut. Model yang digunakan untuk melakukan estimasi adalah model Almost Ideal Demand System (AIDS), dengan menggunakan data dari Indonesia Family Life Survey  gelombang 4 (IFLS 4). Jumlah rumah tangga sumber data yang dianalisis dalam penelitian ini berjumlah 839 rumah tangga.  Hasil penelitian menunjukkan secara parsial harga ikan, harga daging sapi, pengeluaran rumah tangga, wilayah geografi, dan jumlah anggota keluarga berpengaruh terhadap pangsa pengeluaran untuk produk ikan-ikanan, daging ayam, dan daging sapi. Elastisitas permintaan harga permintaan untuk ikan, daging sapi, dan daging ayam masuk dalam kategori inelastis, elastisitas pendapatan untuk daging sapi dan daging ayam masuk kategori elastis, dan ikan mempunyai elastisitas pendapatan yang inelastic.Kata kunci: model Almost Ideal Demand System (AIDS), elastisitas harga permintaan, elastisitas silang, elastisitas pendapatan.